Organizational Culture and Knowledge Sharing Behavior: Moderated Mediation Model - ABBASI, SALIHA GUL; ALAGHBARI, MOHAMMED ABDULRAZZAQ; SHABBIR, MUHAMMAD SALMAN; ABBAS, MAZHAR (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The study aims to examine the indirect relationship of clan organizational culture (COC) and knowledge sharing behavior (KSB) through knowledge sharing opportunity (KSO) and explain the differences in the COC-KSB relationship through KSOs that emerge from a moderating role of informal knowledge governance mechanisms. (IFKGM). Data from 279 university professors from public and private sector universities in Pakistan were collected by grouping the population into strata and drawing convenience samples from it. A moderate mediation model was tested using Process. The results supported the mediating role of KSO between COC and KSB.RESUMEN El estudio tiene como objetivo examinar la relación indirecta de la cultura organizacional del clan (COC) y el comportamiento de intercambio de conocimientos (CIC) a través de la oportunidad de intercambio de conocimientos (OIC) y explicar las diferencias en la relación COC-CIC a través de OIC que surgen de un papel moderador de los mecanismos de gobernanza del conocimiento informal. (MIGC). Se recopilaron datos de 279 profesores universitarios de universidades del sector público y privado en Pakistán agrupando la población en estratos y extrayendo muestras de conveniencia de ella. Se probó un modelo de mediación moderada utilizando Process. Los resultados apoyaron el papel mediador de OIC entre COC y CIC.